Digitalisasi Pemasaran dan Legalitas Merek: Pendampingan Pelaku Usaha Mikro Kecil di Desa Pakukerto Kabupaten Pasuruan: Digitalization of Marketing and Brand Legality: Assistance for Micro and Small Businesses in Pakukerto Village, Pasuruan Regency - Fajrin, Yaris Adhial; Nuryasinta, Radhityas Kharisma; Rusdianasari, Fitri (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2026)
Micro and small businesses in Pakukerto Village, Pasuruan Regency, have great economic potential through various processed food products, herbal drinks, and local handicrafts. However, this potential has not been fully realized due to a lack of understanding of trademark law and limited ability to use digital platforms. This community service activity was organized to improve the legal knowledge and marketing skills of business actors through assistance with trademark registration and training in the use of social media as a professional promotional tool. The activity was carried out using the Asset-Based Community Development Method (ABCD), which utilizes human resources as business actors (skills in producing various local products) and social networks as capital to strengthen a broader marketing capacity. The implementation of activities included identifying the needs of business actors, delivering legal material on the importance of brand protection, training on creating business social media accounts, and providing technical assistance for the brand registration process through the system provided by the Directorate General of Intellectual Property. The results of the activity showed that 80% of participants understood the function of a brand as a business identity and long-term legal protection. A total of 18 of the 30 participants who attended the training expressed their readiness to apply for trademark registration and to start implementing visual content-based marketing strategies. Overall, this activity succeeded in developing the capacity of business actors in Pakukerto Village by encouraging a shift in business behavior toward greater legal awareness and responsiveness to developments in digital marketing.